Characteristics of Pressure Relief Gas Extraction in the Protected Layer by Surface Drilling in Huainan - Xiaozhang Tong; Hu Wen; Xiaojiao Cheng; Shixing Fan; Chunhui Ye; Mingyang Liu; Hu Wang (Advances in Civil Engineering)
To study the behavior of gas extraction from the protected layer by surface drilling, the common characteristics of gas extraction concentration and gas extraction quantity are summarized through the collection of key parameters of surface drilling and a combination of data and figures, with the background of 11−2 coal protection 13−1 coal in the Huainan mining area. The research results show that the flow of pressure relief gas extraction of the protected layer by surface drilling has three stages: a rising period, stable period, and decay period. When the extraction processes of multiple surface wells on the same working face are coordinated, the extraction flow is superimposed, and the extraction volume of surface drilling shows an increasing trend and fluctuates with the location of the drilling. The extraction flow rate before ground drilling is relatively small, and the extraction flow rate increases after ground drilling. This behavior is further confirmed by field observation of mining changes in the protective layer and the expansion and deformation of the protected layer. The periodic variation in the surface drilling and extraction quantity is affected primarily by the mining movement of the working face of the protective layer. Specifically, it is affected by factors such as the mining progress of the working face of the protective layer, mining height, degree of compacted goaf, degree of pressure relief of the protected layer, original gas content, and other measures taken to extract the protected layer.